Soil seed bank composition and implications for ecological restoration in degraded Colorado shrublands - Schroeder, Ryan W. R., author; Paschke, Mark, advisor; Rhoades, Chuck, advisor; Meiman, Paul, committee member; Grant-Hoffman, M. Nikki, committee member; Melzer, Suellen, committee member (Colorado State University. Libraries, 2020)
Soil seed banks of shrub-dominated ecosystems in western North America are poorly understood. The potential of the soil seed bank – the species composition and abundance of seeds – to impact ecological restoration has rarely been considered in ecological restoration of shrublands and could influence management decisions. I analyzed the germinable soil seed bank composition and distribution in two high-conservation priority ecosystems in Colorado. Studies were carried out to characterize seed bank composition and relationship to aboveground vegetation in "undesirable" and "desirable" plant communities; determine if "shrub islands" influence seed bank distribution; and assess the landscape and vertical distribution of the seed bank in a Bromus tectorum L. (cheatgrass) invaded rangeland. For all seed bank studies, soil seed bank samples were collected to a depth of 5 cm and grown in greenhouse conditions to determine the species composition and abundance of germinable seeds. I found that seed bank species richness and Shannon-Wiener diversity (H) did not differ in either shrubland between undesirable sites dominated by non-native vegetation and desirable sites dominated by native vegetation. Total seed abundance in a montane sagebrush shrubland was significantly greater in desirable sites (1401 ± 165 seeds m-2) compared to undesirable sites (588 ± 190 seed m-2). In a salt desert shrubland of the Colorado Plateau, total seed abundance did not differ, but on average non-native species seeds made up more than 60% of the total seed bank in undesirable sites, compared to 40% in desirable sites. In a separate study, shrub islands across Colorado were not associated with increased seed bank species richness or seed abundance compared to adjacent shrub-less interspaces. Differences in seed bank Shannon Wiener diversity (H) varied between shrublands, with salt desert shrublands having significantly greater (p-value < 0.05) seed bank diversity inside of shrub islands compared to shrub-less interspaces. Another study was conducted in a Bromus tectorum L. (cheatgrass) invaded rangeland of the Colorado Plateau to determine the seed bank horizontal and vertical distribution. The germinable soil seed bank had a greater abundance and lower spatial variability of native species seeds (3390 seeds m-2, CV = 75%) than non-native species seeds (1880 seeds m-2, CV: 124%) across the sampled landscape. Non-native species (primarily Bromus tectorum L.) seed were concentrated in the upper 2 cm soil (1294 ± 155, p-value <0.0001), but were found in substantive abundance in the 2 – 5 cm seed bank layer (585 ± 91). In addition to seed bank studies, in the fall of 2018, I established a study in a montane shrubland to test the effectiveness of seeding a high diversity native seed mix (39 species, 1496 PLS m-2) and treatments to increase site heterogeneity to increase native plant species diversity. One growing season following plot establishment, I found that plots that received a high diversity seed mix and those that received heterogeneity treatments had greater seeded species diversity (H) and richness than control plots.
Keywords: public land; salt desert; ecological restoration; soil seed bank; sagebrush